The Development of Generosity From 4 to 6 Years: Examining Stability and the Biopsychosocial Contributions of Children’s Vagal Flexibility and Mothers’ Compassion - Miller, Jonas G.; Kahle, Sarah; Troxel, Natalie R.; Hastings, Paul D. (Frontiers in Psychology, 2020)
Individual differences in children’s prosocial behaviors, including their willingness to give up something of value for the benefit of others, are rooted in physiological and environmental processes. In a sample of 4-year-old children, we previously found evidence that flexible changes in respiratory sinus arrhythmia (RSA) were linked to donation behavior, and that these physiological patterns may support greater sensitivity to the positive effects of compassionate parenting on donation behavior. The current study focused on a follow-up assessment of these children at age 6. First, we examined the stability of individual differences in donation behavior and related parasympathetic nervous system activity from age 4 to age 6. Second, we examined associations between donation behavior and RSA at 6 years. Third, we examined whether the association between children’s RSA and donation behavior at age 6 varied depending on mothers’ compassionate love. We found low to modest stability in donation behavior and RSA reactivity from age 4 to 6. These findings provide preliminary evidence that stable individual differences in altruism, as reflected by generosity, and in some aspects of parasympathetic functioning during opportunities to be prosocial, emerge in childhood. In addition, we found that some of the same associations between donation behavior, RSA and compassionate love that we previously observed in children at 4 years of age continued to be evident two years later at age 6. Greater decreases in RSA when given the opportunity to donate was associated with children donating more of their own resources which, in turn, was associated with greater RSA recovery after the task. Lastly, mothers’ compassionate love was positively associated with donation behavior in children who demonstrated stronger decreases in RSA during the task; compassionate parenting and RSA reactivity may serve as external and internal supports for prosociality that build on each other. Taken together, these findings contribute to the perspectives that individual differences in altruistic behaviors are intrinsically linked to healthy vagal flexibility, and that biopsychosocial approaches provide a useful framework for examining and understanding the environmental and physiological processes underlying these individual differences.